2013
DOI: 10.1037/a0028861
|View full text |Cite
|
Sign up to set email alerts
|

Alone is a crowd: Social motivations, social withdrawal, and socioemotional functioning in later childhood.

Abstract: The primary goals of this study were to test a conceptual model linking social approach and avoidance motivations, socially withdrawn behaviors, and peer difficulties in later childhood and to compare the socioemotional functioning of different subtypes of withdrawn children (shy, unsociable, avoidant). Participants were 367 children, aged 9-12 years. Measures included assessments of social motivations (i.e., self-reported shyness and preference for solitude) and social withdrawal (observations of solitary beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
241
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(272 citation statements)
references
References 106 publications
(207 reference statements)
18
241
3
2
Order By: Relevance
“…Previous research has suggested that parents (Coplan et al, 2004) and even young children (Coplan, Closson, et al, 2007;Coplan, Girardi, et al, 2007) make such distinctions. Our results also support previous empirical works suggesting that unsociability is a comparatively benign form of social withdrawal, particularly in early childhood (Coplan & Weeks, 2010b;Coplan et al, 2004;Harrist et al, 1997). Further, these results support the one previous study of kindergarten teachers' attitudes towards unsociable children .…”
Section: Social Withdrawalsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous research has suggested that parents (Coplan et al, 2004) and even young children (Coplan, Closson, et al, 2007;Coplan, Girardi, et al, 2007) make such distinctions. Our results also support previous empirical works suggesting that unsociability is a comparatively benign form of social withdrawal, particularly in early childhood (Coplan & Weeks, 2010b;Coplan et al, 2004;Harrist et al, 1997). Further, these results support the one previous study of kindergarten teachers' attitudes towards unsociable children .…”
Section: Social Withdrawalsupporting
confidence: 93%
“…Bowker and Raja (2011) suggested that because unsociable children simply prefer to play alone (as opposed to actively avoiding social exchanges because of social anxiety), they may engage in 'just enough' peer interaction to be spared most of the negative consequences of social isolation. Notwithstanding, there is some evidence to suggest that unsociable children are still more prone to being excluded by peers (Coplan & Weeks, 2010b). Accordingly, although our findings suggest that unsociable children may not require teachers' immediate attention or concern, teachers should continue to monitor unsociable children, with an eye towards promoting social skills.…”
Section: Social Withdrawalmentioning
confidence: 74%
See 1 more Smart Citation
“…RRBs are commonly expressed in young typically developing children (Harrop et al 2013), but ASD social withdrawal is extremely rare in typical development (Coplan et al 2013). These findings and TD twin study findings (Robinson et al 2011;Ronald et al 2011) argue against a general invariant coupling of ASD social impairment and ASD RRBs in TD.…”
Section: Criteria Validity Research Approach 2: Do the Two Core Asd Dcontrasting
confidence: 37%
“…Her reduced eye contact does not support the development of her communication skills (reducing her ability to attend, listen, and take turns) and her ability to engage and maintain her engagement with others. Lea is also described as being shy, a trait that is associated with socially withdrawn behaviors and reduced peer relations (Coplan, Rose-Krasnor, Weeks, Kingsbury, & Bullock, 2013). Any tendency to avoid social interactions, speaking, or stuttering may contribute to the development of more covert stuttering behaviors, reduced self-esteem and confidence, and increased impact of the stuttering over the longer term.…”
Section: Questionsmentioning
confidence: 99%